High-voltage wide-temperature electrolyte suitable for ternary lithium metal batteries
The electrolyte constructed using composite solvents and multi-lithium salt systems solves the problems of ion transport and high voltage stability in lithium metal batteries across the entire temperature range, achieving high efficiency, cycle stability, and safety over a wide temperature range, and is suitable for ternary lithium metal batteries.
Patent Information
- Application Number
- CN202610607091.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-06
- Publication Date
- 2026-08-25
AI Technical Summary
Traditional lithium metal battery electrolytes are prone to solidification and ion transport obstruction at low temperatures, and are susceptible to side reactions at high temperatures, leading to a sharp decline in performance. Furthermore, existing temperature control solutions increase system weight and cost, and cannot achieve high-efficiency output across the entire temperature range.
A composite solvent system of methyl butyrate, heptafluorobutyrate, and fluoroethylene carbonate was used, combined with composite lithium salts of LiBF4, LiDFOB, LiFSI, and LiPF6, and film-forming additives of 1,3,6-hexanetrionitrile and ethylene sulfite, to construct a stabilization and protection mechanism at the positive and negative electrode interfaces, thereby improving ion conductivity and electrochemical stability.
It maintains excellent ion conductivity across the entire temperature range of -40℃ to 45℃, features high voltage adaptability of 4.7V and ultra-high rate discharge performance, suppresses lithium dendrite growth, and improves the long-term cycle stability and safety of the battery, making it suitable for high-power fast charging and discharging and high energy density applications.
Smart Images

Figure CN122638587A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium metal battery electrolyte technology, and specifically to a high-voltage, wide-temperature electrolyte suitable for ternary lithium metal batteries. Background Technology
[0002] Lithium metal batteries, with their theoretically high specific capacity and extremely low electrochemical potential, have long been considered a key direction for breaking through the energy density ceiling of existing lithium-ion batteries. However, in practical applications, the adaptability of the electrolyte across the entire temperature range remains a major weakness, especially in low-temperature environments. Traditional carbonate solvents experience significantly enhanced intermolecular forces and a sharp increase in viscosity at temperatures below -10°C, leading to localized solidification or crystallization. This almost completely immobilizes lithium ions in the liquid phase, resulting in a substantial decrease in conductivity. Simultaneously, low temperatures significantly increase charge transfer resistance, and the solid electrolyte interfacial film's resistance to lithium ion transport also rises significantly, leading to a severe reduction in discharge capacity. During charging, uneven deposition is more likely to occur on the lithium metal anode surface, providing a breeding ground for lithium dendrite growth, directly jeopardizing battery safety and lifespan.
[0003] Under high-temperature conditions, traditional electrolytes face the problem of rapidly deteriorating chemical stability. Currently, most commercially available electrolytes use lithium hexafluorophosphate in combination with carbonate solvents. When the temperature exceeds 45°C and the operating voltage is high, the lithium salt itself undergoes autocatalytic decomposition, generating highly reactive byproducts such as phosphorus pentafluoride and hydrofluoric acid. Hydrofluoric acid continuously corrodes the cathode material, accelerating the dissolution of transition metal ions and the irreversible loss of active materials, while also destroying the carefully constructed passivation film on the positive and negative electrode surfaces. Furthermore, high temperatures intensify the oxidation reaction of the carbonate solvent at the high-potential interface of the cathode, not only producing gas but also continuously consuming available active lithium, ultimately leading to a continuous increase in battery internal resistance and a continuous decrease in coulombic efficiency. This series of side reactions results in rapid and irreversible capacity decay, and in severe cases, may even trigger thermal runaway.
[0004] To balance performance at both high and low temperatures, existing solutions often rely on complex, expensive, and weight-increasing battery thermal management systems for active temperature control. This sacrifices the energy density advantage inherent in lithium metal batteries and contradicts the industry's pursuit of high energy efficiency and low cost. While reducing lithium salt concentration or introducing low-viscosity co-solvents can improve low-temperature performance to some extent, this often comes at the cost of sacrificing high-temperature stability and safety, and vice versa. Therefore, developing a novel electrolyte that is resistant to condensation at low temperatures, decomposes at high temperatures, and delivers high efficiency over a wide temperature range is urgently needed. Summary of the Invention
[0005] In order to overcome the above-mentioned defects of the prior art, the embodiments of the present invention provide a high-voltage wide-temperature electrolyte suitable for ternary lithium metal batteries, which solves the problems of traditional electrolytes being prone to solidification at low temperatures, obstructed ion transport, easy occurrence of side reactions at high temperatures, and rapid performance degradation.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] High-voltage, wide-temperature electrolyte suitable for ternary lithium metal batteries, including solvent system, composite lithium salt and film-forming additives;
[0008] The solvent system is composed of methyl butyrate, methyl heptafluorobutyrate, and fluoroethylene carbonate.
[0009] The composite lithium salt includes LiBF4, LiDFOB, LiPF6, and LiFSI;
[0010] The film-forming additives are 1,3,6-hexanetrionitrile and vinyl sulfite.
[0011] Preferably, the mass ratio of methyl butyrate, methyl heptafluorobutyrate and fluoroethylene carbonate is (5.5~6.0):(2.5~3.0):1.5.
[0012] Preferably, the concentration of LiBF4 is 1.8~2.4M and the concentration of LiDFOB is 0.3~0.4M.
[0013] Preferably, the concentration of LiPF6 is 0.2~0.3M.
[0014] Preferably, the amount of 1,3,6-hexanetrionitrile used is 0.4 to 0.5 parts by weight.
[0015] Preferably, the amount of vinyl sulfite used is 0.2 to 0.25 parts by weight.
[0016] Preferably, the concentration of LiFSI is 0.8~1.2M.
[0017] The technical effects and advantages of this invention for high-voltage, wide-temperature electrolytes in ternary lithium metal batteries are as follows:
[0018] 1. This invention utilizes a composite solvent system constructed from methyl butyrate, methyl heptafluorobutyrate, and fluoroethylene carbonate, which combines low melting point, low viscosity, and high electrochemical stability. This ensures that the electrolyte maintains excellent ion conductivity across the entire temperature range of -40°C to 45°C. Specifically, the 1C discharge capacity retention rate can reach 76.8% at -40°C, and stable electrochemical performance can still be maintained at 45°C.
[0019] 2. This invention possesses excellent 4.7V high voltage adaptability and ultra-high rate discharge performance. Through a local high-concentration multi-lithium salt synergistic system, it significantly improves the upper limit of high voltage tolerance and lithium-ion migration efficiency of the electrolyte. It is compatible with high-nickel ternary cathode systems. Under the 4.7V high voltage platform, the 25C discharge capacity retention rate can reach 82.3% in a 25℃ environment, and it can still achieve stable 1C charge and discharge at an extreme low temperature of -40℃, fully meeting the application requirements of high-power fast charging and discharging and high energy density of power batteries.
[0020] 3. This invention constructs a dual-interface stabilization and protection mechanism for positive and negative electrodes. Through the synergistic effect of composite lithium salt and film-forming additives, a dense film is reduced and formed on the surface of the lithium metal negative electrode, effectively inhibiting lithium dendrite growth and dead lithium formation. At the same time, a stable CE film is constructed on the surface of the ternary positive electrode, blocking the oxidative decomposition path of the electrolyte under high voltage and inhibiting the dissolution of the positive electrode transition metal and structural phase transition. Under a high voltage of 4.7V, the capacity retention rate reaches 64% after 780 charge-discharge cycles at 25℃ and 0.5C, 61% after 780 cycles at 45℃ and 0.5C, and as high as 87% after 200 cycles at -40℃ and 0.1C, achieving long-term cycle stability over a wide temperature range.
[0021] 4. This invention is adaptable to both battery safety and industrial mass production. By introducing methyl heptafluorobutyrate as a fluorinated solvent, it optimizes the electrochemical performance of the electrolyte through the electron-withdrawing effect, while also endowing the electrolyte with excellent flame-retardant properties, effectively reducing the risk of battery thermal runaway and improving safety in all scenarios. At the same time, the electrolyte formulation parameters have a wide range of adjustability, and the preparation process is compatible with existing lithium battery electrolyte industrial mass production lines. No new complex equipment is required, and the formulation can be flexibly adjusted according to the application scenario, balancing performance and cost, and has extremely strong industrialization value. Attached Figure Description
[0022] Figure 1 This invention relates to the capacity retention rate of a high-voltage, wide-temperature electrolyte suitable for ternary lithium metal batteries at 4.7V, 0.5C, and 25℃.
[0023] Figure 2 This invention relates to the capacity retention rate of a high-voltage, wide-temperature electrolyte suitable for ternary lithium metal batteries at 4.7V, 0.5C, and 45℃.
[0024] Figure 3 This invention relates to the capacity retention rate of a high-voltage, wide-temperature electrolyte suitable for ternary lithium metal batteries at 4.7V, 0.1C, and -40℃.
[0025] Figure 4 This is a flowchart of the preparation process of high-voltage, wide-temperature electrolyte suitable for ternary lithium metal batteries, as proposed in this invention. Detailed Implementation
[0026] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0027] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitation, an element defined by the phrase "comprising..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0028] Example 1
[0029] This embodiment provides a high-voltage, wide-temperature electrolyte suitable for ternary lithium metal batteries. Specific implementation steps include:
[0030] Experimental materials:
[0031] 5.5 parts by weight of methyl butyrate (MB), 3 parts by weight of methyl heptafluorobutyrate (MHB), 1.5 parts by weight of fluoroethylene carbonate (FEC), 2.4M LiBF4, 0.3M LiDFOB, 0.3M LiPF6, 1.2M lithium bis(fluorosulfonyl)imide (LiFSI), 0.5 parts by weight of 1,3,6-hexanetrionitrile, and 0.2 parts by weight of vinyl sulfite.
[0032] Experimental objective:
[0033] This invention designs a complete formulation of a high-voltage, wide-temperature electrolyte for MHF and establishes a standardized preparation and quality control process.
[0034] Experimental steps:
[0035] S1: In an argon inert atmosphere glove box with water and oxygen contents ≤0.1ppm, methyl butyrate, methyl heptafluorobutyrate, and fluoroethylene carbonate were weighed in sequence at a mass ratio of 5.5:3:1.5. The mixture was placed in a sealed polytetrafluoroethylene reactor and then stirred continuously at 800rpm for 20min at a constant temperature of 25℃ to obtain a uniform, transparent, highly fluid, and flame-retardant mixed solvent matrix.
[0036] S2: Under an inert argon atmosphere and constant temperature of 25°C, LiBF4 was first added to the mixed solvent matrix, and then stirred continuously at 600 rpm for 15 min until completely dissolved. Then, LiFSI was added and stirred continuously at 800 rpm for 20 min to obtain the basic electrolyte. Finally, LiDFOB, LiPF6, 1,3,6-hexanetrionitrile and vinyl sulfite were added to the basic electrolyte in sequence, and stirred continuously at 1000 rpm for 45 min under constant temperature of 25°C to obtain the initial electrolyte.
[0037] S3: Add activated 4A molecular sieve to the initial electrolyte and let it stand for 24 hours at 25°C in a sealed environment to remove water. Then, filter it through a 0.22μm polytetrafluoroethylene microporous membrane for two-stage precision pressure filtration to obtain a refined electrolyte.
[0038] S4: Inject the molecular sieve-treated electrolyte obtained in S3 into the NCM||Li soft-pack battery. Then, place the battery at 25℃ and -40℃ for 25C and 1C discharge tests, respectively. Then, test the retention rate of 4.7V at 25℃ at 0.5C for 780 cycles, at 45℃ at 0.5C for 780 cycles, and at -40℃ at 0.1C for 200 cycles.
[0039] Experimental results: See Table 1 for details.
[0040] Table 1: Test Results of Example 1
[0041] Example 1 Discharge rate at 25℃ (4.7V) 25C discharge capacity retention rate: 82.3% -40℃ discharge rate (4.7V) 1C discharge capacity retention rate: 76.8% Capacity retention after 780 cycles at 45℃, 4.7V, and 0.5C. 61% Capacity retention after 780 cycles at 25℃, 4.7V, 0.5C. 64% -40℃, 4.7V, 0.1C, capacity retention after 200 cycles 87%
[0042] Example 1 uses a 5.5:3:1.5 MB / MHB / FEC mixed solvent system, combined with a high concentration of multiple lithium salts including 2.4M LiBF4, 1.2M LiFSI, 0.3M LiDFOB, and 0.3M LiPF6, and supplemented with 1,3,6-hexanetrionitrile and vinyl sulfite as dual additives. Its superior performance stems from multiple synergistic mechanisms: MB, as a low-melting-point ester solvent, ensures ion conductivity at low temperatures; the fluorinated structure of MHB reduces the binding energy between solvent molecules and lithium ions through electron-withdrawing effects, while also imparting flame-retardant properties to the electrolyte; FEC preferentially reduces on the lithium metal anode surface to form a dense SEI film rich in LiF, effectively inhibiting lithium dendrite growth and dead lithium formation; LiFSI, lithium difluorosulfonylimide, as a composite lithium salt, has extremely high dissociation and ion mobility, providing a large number of freely moving lithium ions, while significantly reducing the overall impedance of the electrolyte; LiDFOB and LiPF6, as functional film-forming additives, form stable CEI and SEI at the positive and negative electrode interfaces, respectively, inhibiting the dissolution of transition metals and structural phase transitions of the NCM cathode under high voltage; 1,3,6-hexanetrionitrile stabilizes the cathode surface through strong coordination, preventing the oxidative decomposition of the electrolyte at a high voltage of 4.7V.
[0043] Example 2
[0044] This embodiment provides a high-voltage, wide-temperature electrolyte suitable for ternary lithium metal batteries. Specific implementation steps include:
[0045] Experimental materials:
[0046] 5.5 parts by weight of methyl butyrate (MB), 3 parts by weight of methyl heptafluorobutyrate (MHB), 1.5 parts by weight of fluoroethylene carbonate (FEC), 1.8M LiBF4, 0.3M LiDFOB, and 0.8M lithium bis(fluorosulfonyl)imide (LiFSI).
[0047] Experimental objective:
[0048] The electrolyte formulation and preparation process were simplified, and the basic wide-temperature electrochemical performance and low-cost mass production adaptability of the core solvent-lithium salt system of this invention in 4.7V ternary lithium metal batteries were verified.
[0049] Experimental steps:
[0050] S1: In an argon inert atmosphere glove box with water and oxygen contents ≤0.1ppm, methyl butyrate, methyl heptafluorobutyrate, and fluoroethylene carbonate were weighed in sequence at a mass ratio of 5.5:3:1.5. The mixture was placed in a sealed polytetrafluoroethylene reactor and then stirred continuously at 600rpm for 15min at a constant temperature of 25℃ to obtain a uniform, transparent, free-flowing, and flame-retardant mixed solvent matrix.
[0051] S2: Under an inert argon atmosphere and constant temperature of 25°C, LiBF4 was first added to the mixed solvent matrix, and then stirred continuously at 500 rpm for 10 min until completely dissolved. Then, LiFSI was added and stirred continuously at 700 rpm for 15 min to obtain the basic electrolyte. Finally, LiDFOB was added to the basic electrolyte in sequence, and stirred continuously at 900 rpm for 30 min under a constant temperature of 25°C to obtain the initial electrolyte.
[0052] S3: Add activated 4A molecular sieve to the primary electrolyte and let it stand for 24 hours at 25°C under sealed conditions to remove water. Then, filter it through a 0.45μm polytetrafluoroethylene microporous membrane under single-stage pressure to obtain a refined electrolyte.
[0053] S4: Inject the molecular sieve-treated electrolyte obtained in S3 into the NCM||Li soft-pack battery. Then, place the battery at 25℃ and -40℃ for 25C and 1C discharge tests, respectively. Then, test the retention rate of 4.7V at 25℃ at 0.5C for 780 cycles, at 45℃ at 0.5C for 780 cycles, and at -40℃ at 0.1C for 200 cycles.
[0054] Experimental results: See Table 2 for details.
[0055] Table 2: Test Results of Example 2
[0056] Example 2 Discharge rate at 25℃ (4.7V) 25C discharge capacity retention rate: 78.6% -40℃ discharge rate (4.7V) 1C discharge capacity retention rate: 71.2% Capacity retention after 780 cycles at 45℃, 4.7V, and 0.5C. 58.3% Capacity retention after 780 cycles at 25℃, 4.7V, 0.5C. 56.7% -40℃, 4.7V, 0.1C, capacity retention after 200 cycles 81.4%
[0057] Example 2 uses the same MB / MHB / FEC (5.5:3:1.5) solvent system as Example 1, but the lithium salts are simplified to 1.8M LiBF4, 0.8M LiFSI, and 0.3M LiDFOB, without the addition of LiPF6, nitrile, or sulfite additives. The reason for its overall performance being lower than Example 1 is as follows: Although the solvent system itself ensures basic wide-temperature-range ion transport capability, and FEC and LiDFOB provide basic interfacial film protection, the lack of LiPF6 leads to insufficient stability of the cathode interfacial film, increased electrolyte oxidation side reactions at high voltages, and the lack of 1,3,6-hexanetrionitrile cathode stabilizing effect exacerbates NCM cathode surface side reactions at 4.7V, increases transition metal dissolution, and accelerates active material loss during cycling; the lack of vinyl sulfite-assisted film formation results in insufficient SEI density, accelerating lithium metal anode interface degradation during long-term cycling.
[0058] Example 3
[0059] This embodiment provides a high-voltage, wide-temperature electrolyte suitable for ternary lithium metal batteries. Specific implementation steps include:
[0060] Experimental materials:
[0061] 6.0 parts by weight of methyl butyrate (MB), 2.5 parts by weight of methyl heptafluorobutyrate (MHB), 1.5 parts by weight of fluoroethylene carbonate (FEC), 2.0 M LiBF4, 0.4 M LiDFOB, 0.2 M LiPF6, 1.0 M lithium bis(fluorosulfonyl)imide (LiFSI), 0.4 parts by weight of 1,3,6-hexanetrionitrile, and 0.25 parts by weight of vinyl sulfite.
[0062] Experimental objective:
[0063] By adjusting the solvent ratio, lithium salt concentration, and preparation process parameters, the low-temperature rate performance of the electrolyte was optimized, and the parameter adaptation range and overall performance balance of the formulation system of this invention were verified.
[0064] Experimental steps:
[0065] S1: In an argon inert atmosphere glove box with water and oxygen contents ≤0.1ppm, methyl butyrate, methyl heptafluorobutyrate, and fluoroethylene carbonate were weighed in sequence according to the mass ratio. They were placed in a sealed polytetrafluoroethylene reactor and then stirred continuously at 1000rpm for 15min under constant temperature of 30℃ to obtain a uniform, transparent, highly fluid mixed solvent matrix with flame retardant properties.
[0066] S2: Under an inert argon atmosphere and constant temperature of 25°C, LiBF4 was first added to the mixed solvent matrix, and then stirred continuously at 700 rpm for 12 min until completely dissolved. Then, LiFSI was added and stirred continuously at 900 rpm for 18 min to obtain the basic electrolyte. Finally, LiDFOB, LiPF6, 1,3,6-hexanetrionitrile and vinyl sulfite were added to the basic electrolyte in sequence, and stirred continuously at 1100 rpm for 40 min under a constant temperature of 30°C to obtain the initial electrolyte.
[0067] S3: Add activated 4A molecular sieve to the initial electrolyte and let it stand for 36 hours at 25°C in a sealed environment to remove water. Then, filter it through a 0.22μm polytetrafluoroethylene microporous membrane for two-stage precision pressure filtration to obtain a refined electrolyte.
[0068] S4: Inject the molecular sieve-treated electrolyte obtained in S3 into the NCM||Li soft-pack battery. Then, place the battery at 25℃ and -40℃ for 25C and 1C discharge tests, respectively. Then, test the retention rate of 4.7V at 25℃ at 0.5C for 780 cycles, at 45℃ at 0.5C for 780 cycles, and at -40℃ at 0.1C for 200 cycles.
[0069] Experimental results: See Table 3 for details.
[0070] Table 3: Test Results of Example 3
[0071] Example 3 Discharge rate at 25℃ (4.7V) 30C discharge capacity retention rate: 79.2% -40℃ discharge rate (4.7V) Capacity retention at 1.5C discharge is 73.5%. Capacity retention after 780 cycles at 45℃, 4.7V, and 0.5C. 61.7% Capacity retention after 780 cycles at 25℃, 4.7V, 0.5C. 59.2% -40℃, 4.7V, 0.1C, capacity retention after 200 cycles 84.6%
[0072] Example 3 adjusted the solvent ratio to MB / MHB / FEC (6.0:2.5:1.5), with a lithium salt combination of 2.0M LiBF4, 1.0M LiFSI, 0.4M LiDFOB, and 0.2M LiPF6, while retaining nitrile and sulfite additives. The mechanism by which its performance falls between Examples 1 and 2 is as follows: increased MB content and higher stirring temperature improved lithium-ion migration rate at low temperatures, but the reduced MHB ratio weakened flame retardancy and high-voltage stabilization; the reduced LiFSI concentration weakened the contribution of ionic conductivity at high rates; the reduced LiPF6 content resulted in insufficient protection of the cathode interface film, leading to slightly faster capacity decay during high-voltage cycling; while high-temperature stirring accelerated dissolution, it may introduce trace side reactions.
[0073] Comparative Example 1
[0074] This embodiment provides a high-voltage, wide-temperature electrolyte for a conventional ternary lithium metal battery, and the specific implementation steps include:
[0075] Experimental materials:
[0076] 10 parts by weight of ethylene carbonate (EC), 10 parts by weight of ethyl methyl carbonate (EMC), 2 parts by weight of fluoroethylene carbonate (FEC), and 1.0 M lithium hexafluorophosphate (LiPF6).
[0077] Experimental objective:
[0078] A benchmark electrolyte based on traditional carbonate solvents and a single lithium salt was constructed to compare and evaluate the performance advantages of the fluorinated solvent and the multi-lithium salt system of this invention under a wide temperature range and high voltage.
[0079] Experimental steps:
[0080] S1: In an argon inert atmosphere glove box with water and oxygen content ≤0.1ppm, weigh ethylene carbonate and ethyl methyl carbonate in a 1:1 mass ratio, add fluoroethylene carbonate, place in a sealed polytetrafluoroethylene reactor, and stir continuously at 600rpm for 15min under constant temperature of 25℃ to obtain a homogeneous and transparent mixed solvent.
[0081] S2: Maintain an inert argon atmosphere and a constant temperature environment of 25°C, add LiPF6 to the mixed solvent, and stir at 500 rpm for 20 minutes until completely dissolved to obtain the initial electrolyte;
[0082] S3: Add activated 4A molecular sieve to the initial electrolyte, let it stand for 12 hours in a sealed environment at 25℃ to remove water, and then filter it under pressure through a 0.22μm polytetrafluoroethylene microporous membrane to obtain a refined electrolyte.
[0083] S4: Inject the electrolyte obtained in S3 into the NCM||Li pouch cell and test the rate discharge performance at 25℃ and -40℃, as well as the cycle performance at a high voltage of 4.7V.
[0084] Experimental results: See Table 4 for details.
[0085] Table 4: Test Results of Comparative Example 1
[0086] Comparative Example 1 Discharge rate at 25℃ (4.7V) 25C discharge capacity retention rate: 65.4% -40℃ discharge rate (4.7V) 1C discharge capacity retention rate: 45.2% Capacity retention after 780 cycles at 45℃, 4.7V, and 0.5C. 38.5% Capacity retention after 780 cycles at 25℃, 4.7V, 0.5C. 42.1% -40℃, 4.7V, 0.1C, capacity retention after 200 cycles 62.8%
[0087] Comparative Example 1 uses a traditional carbonate solvent EC / EMC (1:1) combined with FEC and a single LiPF6 lithium salt. The reason its performance is significantly lower than that of the embodiments of this invention is as follows: the viscosity of the EC / EMC carbonate solvent increases sharply at low temperatures, even partially solidifying, leading to a precipitous drop in ionic conductivity and severe degradation of discharge performance at -40℃; LiPF6 has poor thermal stability and easily decomposes to generate PF5 and HF at high temperatures and high voltages (45℃). HF acid-etches the cathode material and damages the interfacial film, accelerating the dissolution of transition metals and the consumption of active lithium, resulting in rapid capacity decay at high temperatures; single LiPF6 cannot construct a stable positive and negative electrode dual-interfacial film. At a high voltage of 4.7V, the carbonate solvent continuously oxidizes and decomposes on the cathode surface, leading to severe lithium dendrite growth and dead lithium accumulation on the negative electrode side, reducing coulombic efficiency, and resulting in a capacity retention rate far lower than the multi-lithium salt synergistic film-forming system of this invention.
[0088] refer to Figure 4 The flowcharts, comparing the examples and comparative examples, show that Example 1 achieves an optimal balance between high rate capability and long cycle life over a wide temperature range. Through a sophisticated design of a dual-interface film stabilization system with high-concentration multi-lithium salt synergy and dual additives, it significantly improves high and low temperature cycle stability and rate performance at 4.7V, making it suitable for ternary lithium metal battery systems with stringent requirements for full temperature range, high voltage, and long lifespan. Example 2, while simplifying the formulation and reducing costs, suffers from significantly insufficient cycle life and high-voltage stability. Example 3 improves low-temperature rate capability by adjusting the solvent ratio and lithium salt content, but its high-voltage cycle performance is inferior to Example 1. The comparative examples highlight the severe performance imbalance at high and low temperatures and the functional limitations of traditional carbonate and single LiPF6 systems, particularly the uncontrolled interfacial side reactions at high voltages.
[0089] refer to Figure 1 , 2 Figure 3 shows the results of the cycling test. The high-voltage wide-temperature electrolyte exhibits excellent long-term cycling stability at three temperature dimensions: 25℃, 45℃ and -40℃. Figure 1 The results show that under conditions of 25℃, 4.7V high voltage, and 0.5C charge-discharge, the battery retains 64% of its capacity after 780 cycles, indicating that the electrolyte and electrode interface are stable at room temperature and that the side reactions caused by high voltage are effectively suppressed. Figure 2 The results show that even when the temperature is raised to a high temperature of 45°C, after 780 cycles in an operating environment of 4.7V and 0.5C, the capacity retention rate can still be maintained at 61%, indicating that the system significantly improves the traditional problems of lithium salt decomposition and cathode material corrosion at high temperatures. Figure 3 The low-temperature performance cycle test chart shows that, in an extremely cold environment of -40℃, under a low current charge-discharge mode of 4.7V and 0.1C, the capacity retention rate is as high as 87% after 200 cycles. This proves that the solvent system constructed from low-melting-point esters and fluorinated solvents has successfully broken through the bottleneck of easy solidification of electrolyte and sluggish ion transport at low temperatures.
[0090] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of protection of the claims.
[0091] In conclusion, the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A high-voltage, wide-temperature electrolyte suitable for ternary lithium metal batteries, characterized in that, This includes solvent systems, composite lithium salts, and film-forming additives; The solvent system is composed of methyl butyrate, methyl heptafluorobutyrate, and fluoroethylene carbonate. The composite lithium salt includes LiBF4, LiDFOB, LiPF6, and LiFSI; The film-forming additives are 1,3,6-hexanetrionitrile and vinyl sulfite.
2. The high-voltage, wide-temperature electrolyte suitable for ternary lithium metal batteries as described in claim 1, characterized in that, The mass ratio of methyl butyrate, methyl heptafluorobutyrate and fluoroethylene carbonate is (5.5~6.0):(2.5~3.0):1.
5.
3. The high-voltage, wide-temperature electrolyte suitable for ternary lithium metal batteries as described in claim 1, characterized in that, The concentration of LiBF4 is 1.8~2.4M, and the concentration of LiDFOB is 0.3~0.4M.
4. The high-voltage, wide-temperature electrolyte suitable for ternary lithium metal batteries as described in claim 1, characterized in that, The concentration of LiPF6 is 0.2~0.3M.
5. The high-voltage, wide-temperature electrolyte for ternary lithium metal batteries as described in claim 1, characterized in that, The amount of 1,3,6-hexanetrionitrile used is 0.4 to 0.5 parts by weight.
6. The high-voltage, wide-temperature electrolyte for ternary lithium metal batteries as described in claim 1, characterized in that, The amount of vinyl sulfite used is 0.2 to 0.25 parts by weight.
7. The high-voltage, wide-temperature electrolyte suitable for ternary lithium metal batteries as described in claim 1, characterized in that, The concentration of LiFSI is 0.8~1.2M.
